Who should Issue a Permit for the Memorial? Administrative Law as a Platform for the Conflict over the Construction of the Monument to the Victims of the Smoleńsk Tragedy in Warsaw - Piotr Eckhardt (Politologija)
Circles associated with the ruling Law and Justice party decided to build a monument to the victims of the crash of a Polish government airplane in Smoleńsk on April 10, 2010 in Piłsudski Square in Warsaw. However, the authorities of that city, associated with the political opposition, were not positive about the project. Government bodies instrumentally used (and even abused) existing institutions of administrative law to build the monument despite the opposition of the local self-government. First, control over Piłsudski Square was taken away from the city authorities. Then the square was declared a closed area of military importance so that the city authorities could not make it difficult to obtain permission to build the monument. Finally, the Polish parliament created special legislation to make it more difficult to remove the monument in the future.